Chassis dynamometer to analyse performance of electric two wheelers (ETW) - Daing Mohamad Nafiz, Daing Idris; Ahmad Fitri, Yusop; F., Basrawi; Mohd Azri Hizami, Rasid; Muhammad Hadi, Hassan; Samad, Rahin (2018)
In recent years, electric motorcycles are emerging as one of the alternative to improve sustainability of transportation energy and air quality especially in urban areas. Although electric motorcycles are environmentally friendly, they underperform compared with gasoline motorcycles in many respects, particularly in speed and cruise distance between refueling and recharging. Currently, dynamometers for vehicles are generally divided into chassis-type and engine-type dynamometers. In a chassis-type dynamometer, the rear tire will make contact with the rollers. The rollers will be coupled directly to the dynamometer in order to simulate the load on the engine. In the case of an engine-type dynamometer, it is quite inconvenient to disassemble a two-wheeler electric motorcycle before it can be tested on an engine-type test platform.